From the Lecture Hall to the Food Office: Best Practice in Stunting Management and Food Safety Supervision in Pontianak City - Nawawi Nawawi; Silveter Donata Melania; Meri Andani; Milanda Milanda; Veronika Jenita (LPPM Universitas PGRI Semarang, 2026)
Higher education in the era of Industry 4.0 and Society 5.0 is expected to produce graduates who are competent, adaptive, and work-ready. The Merdeka Belajar Kampus Merdeka (MBKM) certified internship offers one pathway toward this goal, yet how such internships integrate with partner institutions’ real needs and what students actually gain still deserve closer documentation. This article describes and analyses the participation of Biology Education students of Universitas PGRI Pontianak in food security and food safety programmes at the Food, Agriculture and Fisheries Office (DPPP) of Pontianak City, covering the Diverse, Nutritious, Balanced and Safe Food (B2SA) programme for stunting prevention and fresh-food safety supervision. Using a descriptive qualitative case-study approach, data were collected over four months through participatory observation and documentation, then analysed following the Miles, Huberman and Saldaña interactive model. The findings show that students were actively involved in preparing and distributing B2SA food packages, delivering nutrition education, taking anthropometric measurements, conducting qualitative formalin and pesticide-residue tests on fresh produce, and supporting administrative tasks. Through these activities they built a contextual understanding of food, nutrition and food-safety issues while developing both technical and non-technical skills, and translated their experience into a community-based follow-up plan. The internship proved effective in connecting classroom theory with field practice and produced mutual benefits for the students and the partner institution, supporting its continuation with structured monitoring and evaluation.